Hydrodynamic limit of the Robinson–Schensted–Knuth algorithm. Issue 1 (11th May 2021) - Marciniak, Mikołaj
Abstract: We investigate the evolution in time of the position of a fixed number in the insertion tableau when the Robinson–Schensted–Knuth algorithm is applied to a sequence of random numbers. When the length of the sequence tends to infinity, a typical trajectory after scaling converges uniformly in probability to some deterministic curve.